2015
DOI: 10.1590/0037-8682-0184-2015
|View full text |Cite
|
Sign up to set email alerts
|

Triatominae (Hemiptera, Reduviidae) in the Pantanal region: association with Trypanosoma cruzi, different habitats and vertebrate hosts

Abstract: Introduction:The transmission cycle of Trypanosoma cruzi in the Brazilian Pantanal region has been studied during the last decade. Although considerable knowledge is available regarding the mammalian hosts infected by T. cruzi in this wetland, no studies have investigated its vectors in this region. This study aimed to investigate the presence of sylvatic triatomine species in different habitats of the Brazilian Pantanal region and to correlate their presence with the occurrences of vertebrate hosts and T. cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…During a study of coati ecology, Santos et al [ 55 ] collected Triatoma sordida ( n = 13) and Rhodnius stali ( n = 2) from seven coati resting nests. Additionally, 21 nymphs of all stages were collected from these nests, confirming these as suitable habitats for triatomines.…”
Section: The Coati N Nasua and Other Carnivorementioning
confidence: 99%
“…During a study of coati ecology, Santos et al [ 55 ] collected Triatoma sordida ( n = 13) and Rhodnius stali ( n = 2) from seven coati resting nests. Additionally, 21 nymphs of all stages were collected from these nests, confirming these as suitable habitats for triatomines.…”
Section: The Coati N Nasua and Other Carnivorementioning
confidence: 99%
“…Triatomine bugs living in close association with free-ranging coatis have been observed in the Nhecolândia region [ 20 , 21 ]. Herein, we observed that the majority of these nests sheltered triatomine bugs infected with T. cruzi , suggesting that coatis might be infected early in these nests through two mechanisms, the oral route and the contaminative route.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitin tests revealed that these bugs fed on coati, bird, rodent and marsupial species [ 20 ]. Additionally, this habitat might act as a point of convergence and dispersion for triatomine bugs and mammal hosts infected with T. cruzi in the Pantanal region [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of this species in nests is already known, as it has recently been found in bird and mammal nests in the Brazilian Pantanal region 2,9 . However, the discovery in poultry nests, such as those of G. gallus, generates a concern due both to the proximity of these animals to humans, especially species that have a high frequency of infection by T. cruzi 10 , and the findings of the present study, because the two specimens collected tested positive for trypanosomatids, although no molecular analysis was performed to confirm the species.…”
mentioning
confidence: 92%
“…Triatominae (Hemiptera, Reduviidae, Triatominae) are insects of medical importance, since they can transmit Trypanosoma cruzi, the etiologic agent of American trypanosomiasis, also known as Chagas disease 1 , which affects approximately 12 million people, with a further 60 million people living in areas of risk around the world 2 .…”
mentioning
confidence: 99%